A contribution to the chronology of S-fibulae in Slovenia - Milavec, Tina (Arheološki vestnik, 2007)
The appearance of S-fibulae in the 6th century is usually connected with the Lombards because S-fibulae were the most common type of small fibulae worn by Lombard women. Recent research has shown that this connection is often not justified.In this paper, 41 S-fibulae from Slovenia are described, the majority of them from the necropolis v Lajhu in Kranj (31 fibulae). Work on the S-fibulae has given unexpected results as far as composition of the graves is concerned. The combinations of grave goods are not comparable to standard combinations usually found in the area and time period under study, for example, the standard combinations of four fibulae (one pair of small and one pair of large fibulae) in women’s graves. Also, typological characteristics of Slovenian S-fibulae have surprisingly shown a connection with the pre-Pannonian phase of Lombard settlement in Europe and not, as previously expected, with the generation of Lombards which had moved from the Pannonian plain to Italy in the year 568. Regarding the geographical position of Kranj these were rather surprising results and would deserve further attention.